Increasing Employee Engagement Through Workplace Happiness: A Quality of Work Life Mediation Study - Agustiani, Titin; Mora, Linda; Ibad, Choirul (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Employee engagement rates in several Indonesian companies remain very low, including at PT Pupuk Kujang, which aims for an employee engagement rate above 85%. Factors affecting employee engagement levels include quality of work life and workplace happiness. Therefore, this study aims to determine whether workplace happiness mediates the effect of quality of work life on employee engagement at PT Pupuk Kujang. The study involved 191 employees selected through convenience sampling and used a correlational quantitative approach with a survey type. The instruments used were the Development Dimensions International (DDI) scale, Quality of Working Life (QoWL), and Happiness at Work Measurement Scale. Data were analyzed using assumption tests and path analysis regression models. The study findings reveal that quality of work life has a direct and significant effect on employee engagement (estimate = 0.447, p < 0.001). Quality of work life positively and significantly affects workplace happiness (estimate = 0.076, p < 0.001). Additionally, workplace happiness significantly affects employee engagement (estimate = 0.365, p < 0.001). Further analysis shows that workplace happiness can serve as a partial mediator in the effect of quality of work life on employee engagement (estimate = 0.200, p < 0.001). The implications of this study indicate that enhancing workplace happiness can strengthen the effect of quality of work life on employee engagement at PT Pupuk Kujang.Angka employee engagement di beberapa perusahaan Indonesia masih sangat rendah, salah satunya di PT Pupuk Kujang yang menginginkan angka employee engagement di atas 85%, faktor yang memengaruhi tingkat employee engagement itu sendiri diantaranya quality of work life dan workplace happines. Maka penelitian ini bertujuan untuk mengetahui apakah terdapat peran mediasi workplace happiness pada pengaruh quality of work life terhadap employee engagement di PT Pupuk Kujang. Penelitian ini melibatkan 191 karyawan yang dipilih melalui metode convenience sampling dan menggunakan pendekatan kuantitatif korelasional berjenis survei. Instrumen yang digunakan adalah skala Development Dimensions International (DDI), Quality of Working Life (QoWL), Happiness at Work Measurement Scale. Data dianalisis menggunakan uji asumsi dan regresi model analisis jalur (path analysis). Temuan penelitian mengungkapkan bahwa quality of work life berpengaruh langsung dan signifikan terhadap employee engagement (estimate = 0,447, p < 0,001). Quality of work life berpengaruh positif dan signifikan terhadap workplace happiness (estimate = 0,076, p < 0,001). Selain itu, workplace happiness berpengaruh signifikan terhadap employee engagement (estimate = 0,365, p < 0,001). Analisis lebih lanjut menunjukkan bahwa workplace happiness dapat berperan sebagai mediasi parsial pada pengaruh quality of work life terhadap employee engagement dengan (estimate = 0,200, p < 0,001). Implikasi dari penelitian ini menunjukkan bahwa meningkatkan workplace happiness dapat memperkuat pengaruh quality of work life terhadap employee engagement di PT Pupuk Kujang.